Comparison of Led Fluorescent Microscopy and the Gene Xpert MTB/RIF Assay in Diagnosis of Pulmonary and Extrapulmonary Tuberculosis (Tribhuvan University Journal of Microbiology, 2019)
Objectives: The objective of this study was to evaluate Gene Xpert MTB/RIF Assay and anid fast staining (AFB) for rapid detection of Mycobacterium tuberculosis in specimen of patients suspected of pulmonary tuberculosis (PTB) and extra pulmonary tuberculosis (EPTB).Methods: A comparative cross-sectional study of 400 samples (PTB-365 and EPTB-35) of patients visiting National Tuberculosis Centre (NTC) was conducted from July 2018 to December 2018. Gene Xpert MTB/ RIF Assay, smear microscopy were performed under standard guideline inside biosafety cabinet class II. The result obtained from both the tests were analyzed using SPSS 20.0 software and Excel 2019.Results: Of the total samples, 18% (72/400) and 39% (156/400) were positive by AFB smear microscopy and Xpert MTB/RIF assay respectively. Prevalence of MTB positive was highest in the age group 35-44 years, 33 cases (17.74%) were detected in total, with a male to female ratio of 2.3:1. Pleural fluid, pus, and CSF fluid also yielded positive results with the Gene Xpert MTB/RIF assay accounting 1.28%, 0.64% and 1.28% of MTB positive case respectively. Rifampicin resistance was observed in 1.28% of the cases.Conclusion: The key findings of this study suggest that Gene Xpert test should be implemented as primary diagnostic test for PTB and EPTB.